2013
DOI: 10.1016/j.psychres.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Treatment-Emergent Activation and Suicidality Assessment Profile (TEASAP) in youth with OCD

Abstract: This study evaluated the psychometric properties of the treatment-emergent activation and suicidality assessment profile (TEASAP) in a clinical sample of 56 youth ages 7 to 17 with obsessive compulsive disorder (OCD) who participated in a double-blind randomized controlled trial. The 38-item TEASAP demonstrated good internal consistency for its total score (α = 0.93) and adequate to good performance for its five subscale scores (α = 0.65 to 0.92). One week test-retest stability (N = 18) was adequate (Intraclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Echoing similar analyses reported by Bussing and colleagues (2013), number of comorbidities was not significantly associated with TEASAP ratings (0.11, p = 0.25) in the entire sample. A higher number of comorbidities was weakly associated with higher daytime activity levels (0.35, p < 0.05), but not night-time activity levels (−0.01, p = 0.97), which aligned findings that showed that number of comorbidities had no association with any sleep variables.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Echoing similar analyses reported by Bussing and colleagues (2013), number of comorbidities was not significantly associated with TEASAP ratings (0.11, p = 0.25) in the entire sample. A higher number of comorbidities was weakly associated with higher daytime activity levels (0.35, p < 0.05), but not night-time activity levels (−0.01, p = 0.97), which aligned findings that showed that number of comorbidities had no association with any sleep variables.…”
Section: Resultssupporting
confidence: 77%
“…The TEASAP (Bussing et al, 2013) is a parent-rated assessment of activation symptom severity that captures five identified symptom clusters related to Activation Syndrome: (1) Irritability (9 items), (2) Akathisia/Hyperkinesis/Somatic Anxiety (6 items), (3) Disinhibition/Impulsivity (7 items), (4) Mania (10 items), and (5) Self-injury/Suicidality/Harm to others (6 items). Parents rate the child’s behavior in the past week, considering frequency and impairment associated with the behavior on a 4-point Likert-style scale (0 = none; 1 = mild; 2 = moderate; and 3 = severe).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variability of this estimate is largely due to an absence of any comprehensive assessment measure of AS. Recently, the Treatment-Emergent Activation and Suicidality Assessment Profile (TEASAP) was developed to remedy this problem, providing a psychometrically validated method to comprehensively assess AS in children and adolescents receiving SSRI treatment (Bussing et al, 2013). The measure identifies five clusters of SSRI-induced side effects, including irritability, akathisia, disinhibition, mania, and self-harm.…”
Section: Introductionmentioning
confidence: 99%